Imagens de arquivo e narrativas contemporâneas em Hemingway & Gellhorn: quando o real e a ilusão se fundem - Monica Martinez; Paulo Celso da Silva (Doc On-Line: Revista Digital de Cinema Documentário, 2012)
The film Hemingway & Gellhorn, produced in 2012 for television byHBO, premiered on HBO Brazil in October 27, 2012. The work contributes to the debateabout the thin line between reality and illusion, since the archival footage is used in thecontext of a fictional narrative. The analysis of 30 reviews about the film, published in theAmerican media, reveals the predominance of personal vision of the critics as well as thelack of consensus among them about the use of documentary images in contemporaryfiction films.